The role of school in the life of children growing up in ethnically divided post-conflict communities - Čorkalo Biruški, Dinka (Array, 2011)
Social context is one of key factors in formation of inter-group attitudes. When the context is as such that a community is fundamentally divided according to the ethnic key, other social cues may be of less importance in shaping social dynamics of the community. As a result of the recent war, the city of Vukovar (Croatia) turned into the ethnically divided community where even schools became divided along the ethnic lines. Although the school is not the only socializing agent, it is a major formative agent throughout the period of childhood and adolescence. By being divided in the schools and not encouraged to communicate beyond the ethnic lines outside the school, children are prevented from having contacts, which is a basic condition for normalization of inter-group relations. The present study explores a set of intergroup attitudes in the context of everyday realities of separate schooling: (1) attitudes towards school integration ; (2) attitudes toward social integration of children outside the schools ; (3) tolerance of diversity ; (4) attitudes toward assimilation of ethnic minorities ; (5) contacts with outgoup, and (6) tendency to discriminate the outgoup members. Two independent samples of school children of Croatian (majority) and Serbian (minority) ethnic background (N= 719 and N= 815) aged 12-16 and their parents participated in the study at two points in time: in 2001 and 2007. Results revealed different pattern of attitudes depending on the majority and minority status at both time points, but also depending on the social role of the participants. Generally more positive intergroup attitudes of parents seem to corroborate a notion that children who do not have an experience of a previously integrated social life in the community are more prone to express negative intergroup attitudes and behavioral tendencies. Our results also show only minor improvements in intergroup attitudes among children over the period of six years, indicating potentially detrimental effects of social division and separate schooling on young people’s inter-ethnic attitudes and relations. We will discuss the potentials of school as a crucial social agent in supporting social reconstruction processes and promoting better interethnic relations.